Danshensu for Myocardial Ischemic Injury: Preclinical Evidence and Novel Methodology of Quality Assessment Tool - Bao, Xiao-yi; Zheng, Qun; Tong, Qiang; Zhu, Peng-chong; Zhuang, Zhuang; Zheng, Guo-qing; Wang, Yan (Frontiers in Pharmacology, 2018)
Abstract Background: Danshensu (DSS) possesses unique bioactivity on the cardiovascular system. However, there is a lack of systematical summary of DSS for acute myocardial ischemia injury and no quality assessment tool for the systematical review of cell experiments. Here, we aimed to assess the preclinical evidences and possible mechanisms of DSS for myocardial ischemia injury, and to develop a quality assessment tool for the systematical review of cell experiments. Methods: Thirty-two studies with 473 animals and 134 cells were identified by searching 7 databases. All data analysis was performed using RevMan 5.3. CAMARADES 10-item checklist was used to assess the methodological quality of animal experiments. A new 10-item checklist was first developed to assess the methodological quality of cell studies. Results: The score of study quality ranged from 3 to 7 points in animal studies, while the cell studies scored 3 to 6 points. Meta-analysis showed that DSS had significant effects on reducing myocardial infarct (MI) size in vivo, and increasing cell viability and reducing apoptosis rate in vitro compared with controls (P< 0.01). The possible mechanisms of DSS for MI are improving circulation, antioxidant, anti-apoptosis, anti-inflammatory, promoting angiogenesis, anti-excessive autophagy, anti-calcium overload, and improving energy metabolism. Conclusions: DSS could exert cardioprotective effect on myocardial ischemia injury, and thus is a probable candidate for further clinical trials andtreatment of AMI . In addition, the newly devloped 10-item checklist for assessing methodological quality of cell study that recommened to use the sysmatic review of cell studies.